Work Life and Mental Health, Employees’ Perspective - Leifson, Anita Krüger (UiT Norges arktiske universitet, 2015)
Abstract Minor mental disorders are widespread and may have significant consequences for the individual, their family and colleagues, as well as for the society (Mykletun & Knudsen, 2009). The purpose of this study was to examine the challenges and experiences employees with mental health problems have with maintaining employment. Hopefully, this will provide an increased understanding of how employees with mental health problems may be included and cared for at the workplace. This was investigated by interviewing twelve employees from the age of 18 to 67 years, who had minor mental health problems to the extent that they received treatment from specialised health services. The informants were recruited by displaying posters in public places in Tromsø and by mail to patients at the Adult Psychiatric Outpatient Clinic in Tromsø, at the University Hospital of North Norway. Qualitative research interview as described by Kvale & Brinkmann (2009) was applied. Interpretative Phenomenological Analysis (Smith & Osborne, 2008) was used for analysing the results. The results were discussed in light of relevant literature, Norwegian laws and psychological theories. The identity as individual and employee is preferred to be sustained, the use of diagnoses and labels should be avoided in the workplace. It is important to consider the vulnerabilities that lie in the employees with mental health problems to be able to secure inclusiveness. Social support should be balanced to avoid disempowerment and to promote development and recovery. It is valuable to consider motivating and challenging aspects in the work environment to secure inclusiveness and care for employees with mental health problems. The employers are ascribed the responsibility to tend, respect and acknowledge their employees, the employees have a responsibility to notify sickness and lack of support. This is challenged by capacity and knowledge. Sammendrag Lettere psykiske lidelser er utbredte, og kan ha betydelige konsekvenser for individ, familie, ...